1993
DOI: 10.1128/aac.37.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir susceptibilities of herpes simplex virus strains isolated from solid organ transplant recipients after acyclovir or ganciclovir prophylaxis

Abstract: We determined the acyclovir (ACV) susceptibilities of herpes simplex virus (HSV) isolates (n = 18) recovered from solid organ transplant patients after antiviral prophylaxis with ACV or ganciclovir. All isolates tested were susceptible to ACV (50%Yo inhibitory concentration, <1 FLM). A clinical review of patients with HSV disease showed that all improved with specific anti-HSV therapy, and no recurrences were reported.Recurrent infections with herpes simplex virus (HSV) are a major cause of morbidity in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 21 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Thymidine kinase is a phosphotransferase enzyme that incorporates dGTP analogs in the presence of ganciclovir instead of cellular dGTP and leads to the blockade of cellular replication (Boivin et al, 1993). But the low transduction efficiency neither improved tumor progression nor the overall survival time (Ram et al, 1993 1994; Gunzburg et al, 1995).…”
Section: Viral Vectors Targeting Astrocytes: Applications For Brain Dmentioning
confidence: 99%
“…Thymidine kinase is a phosphotransferase enzyme that incorporates dGTP analogs in the presence of ganciclovir instead of cellular dGTP and leads to the blockade of cellular replication (Boivin et al, 1993). But the low transduction efficiency neither improved tumor progression nor the overall survival time (Ram et al, 1993 1994; Gunzburg et al, 1995).…”
Section: Viral Vectors Targeting Astrocytes: Applications For Brain Dmentioning
confidence: 99%
“…Acyclovir resistance may arise from mutations in the genes for thymidine kinase or DNA polymerase (453). Acyclovir-resistant isolates have been associated with progressive and severe disease in immunocompromised patients, particularly those with AIDS, and it is possible that resistance will become a problem for transplant recipients in years ahead (187), although this has not occurred to date (61).…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…Ljungman et al (84) described three bone marrow transplant patients who developed severe pneumonia due to ACV-resistant HSV that emerged during the course of ACV treatment. By contrast, Boivin et al (12) recently showed that, for solid organ transplant patients, prophylaxis with ACV or GCV did not result in emergence of ACV-resistant HSV variants and that HSVrelated disease in these patients responded to antiviral therapy without subsequent recurrences. These authors suggest that the relatively lower degree of immunosuppression in these patients compared with AIDS and bone marrow transplant patients, and the relatively high-dose ACV regimen used in prophylaxis, may explain the lack of resistance development.…”
Section: Introductionmentioning
confidence: 91%